2014
DOI: 10.1038/ncomms5420
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced electrical activities and insulin secretion in pancreatic islet β-cells are modulated by CFTR

Abstract: The cause of insulin insufficiency remains unknown in many diabetic cases. Up to 50% adult patients with cystic fibrosis (CF), a disease caused by mutations in the gene encoding the CF transmembrane conductance regulator (CFTR), develop CF-related diabetes (CFRD) with most patients exhibiting insulin insufficiency. Here we show that CFTR is a regulator of glucose-dependent electrical acitivities and insulin secretion in β-cells. We demonstrate that glucose elicited whole-cell currents, membrane depolarization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
162
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(171 citation statements)
references
References 43 publications
(55 reference statements)
3
162
2
4
Order By: Relevance
“…Recently, loss of CFTR function in cell lines and cultured rodent/ferret and human islets has been reported to impair insulin secretion (11)(12)(13)(14) and augment glucagon secretion (15,16), suggesting that loss of CFTR function in islet endocrine cells contributes to CFRD via intrinsic disruption of β and α cell stimulus-secretion coupling. Conversely, studies of humans and CF animal models have suggested that CFRD results from CF-induced pancreatic autolysis, inflammation, and reduction of β cell mass (17)(18)(19)(20) causing insufficient islet hormone secretion (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, loss of CFTR function in cell lines and cultured rodent/ferret and human islets has been reported to impair insulin secretion (11)(12)(13)(14) and augment glucagon secretion (15,16), suggesting that loss of CFTR function in islet endocrine cells contributes to CFRD via intrinsic disruption of β and α cell stimulus-secretion coupling. Conversely, studies of humans and CF animal models have suggested that CFRD results from CF-induced pancreatic autolysis, inflammation, and reduction of β cell mass (17)(18)(19)(20) causing insufficient islet hormone secretion (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] The most lethal clinical manifestation of CF is lung disease, with chronic inflammation and infection causing damage to the organ with deteriorating lung function. 22 Other clinical manifestations of CF include CF-related diabetes, 26,27 liver disease, gall bladder disease, intestinal disease, bone disease 28 and abnormalities in fatty acid metabolism. 29 However, the molecular mechanisms underlying the pathogenesis of these CF-related diseases remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way as in humans, the glucose abnormalities progress with age in the Cftrnull animals as pancreatic fibrosis worsens. In contrast to the current belief that insulin insufficiency in CFRD is mainly due to the destruction of the pancreatic islets, the study of Guo et al (45) revealed no significant difference in pancreatic islet morphology between CFTR WT and F508del mice, indicating that the observed defect in insulin secretion in CF may not be caused by structural alteration in the islets. Of note, CFRD may start in CF patients at ages as children or juveniles with the absence of islet destruction.…”
Section: B-cell-specific Dysfunctionmentioning
confidence: 69%
“…Evidence reveals a role of CFTR in glucose-induced electrical activities and insulin secretion in b-cells (45). CFTR is important for rapid exocytosis of primed granules important for first-phase insulin release (46) (Fig.…”
Section: B-cell-specific Dysfunctionmentioning
confidence: 99%